Frosted branch angiitis : Clinical findings and Spectralis OCT follow-up - Bergua, A.; Galiano, M.; Hohberger, B.; Rudolph, Michael (Ophthalmologe, 2016)
Frosted branch angiitis is a special form of retinal vasculitis, which has only rarely been reported in the literature. Although the majority of cases of frosted branch angiitis are idiopathic, a systematic clinical work-up should be done in order to exclude other causes, such as infectious and autoimmune diseases. The aim of this study was to correlate the clinical findings with the images obtained during follow-up by spectral domain optical coherence tomography (OCT).
EVALuna2:21248